EFFECTS OF VITAMIN D SUPPLEMENTATION DURING PREGNANCY ON NEWBORNS AND INFANTS: AN INTEGRATIVE REVIEW - Letícia Veríssimo Dutra; Fabíola Isabel Suano de Souza; Tulio Konstantyner (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To identify the effects of vitamin D supplementation during pregnancy on newborns and infants. Data sources: The present study is an integrative review of literature based on clinical trials published in journals indexed in the PubMed and Web of Science databases. Two searches were carried out, starting with the association (and) of the health term "vitamin D" with "pregnancy". In the search for information, selection criteria were established, and there was no language limitation and year of publication. Data synthesis: The final selection resulted in 44 clinical trials, most of which were randomized and double blind, which were carried out in outpatient clinics, referral hospitals and universities, mainly in Europe. The samples studied were predominantly of newborns. In these 44 trials, 23 types of different doses of vitamin D during pregnancy, with different doses, regimens and times of use, and 14 different outcomes were studied in newborns (NB) and infants. Of the 44 studies performed, 35 showed statistically significant beneficial effects of vitamin D supplementation during pregnancy on newborns and infants compared to control groups. Conclusions: Vitamin D supplementation during pregnancy for at least three months before delivery has the potential of positively influencing calcium metabolism, physical growth and immune system development in newborns and infants. However, there is insufficient knowledge to define the optimal dose and to guarantee the absence of possible long-term adverse effects.